The chemotherapeutic drug 5-fluorouracil induces apoptosis in mouse thymocytes in Vivo via activation of the CD95(APO-1/Fas) system - Eichhorst, Sören; Weigand, Markus A.; Krammer, Peter H. (Cancer research, 2001)
The CD95/CD95 ligand (CD95L) system has been shown to mediate chemotherapeutic drug-induced apoptosis in vitro. However, the contribution of the CD95 pathway to drug-induced apoptosis is controversial. We have shown previously that 5-fluorouracil (5-FU) induces apoptosis in vitro via the activation of the CD95/CD95L system. To study the effects of the chemotherapeutic drug 5-FU and the contribution of the CD95 system to 5-FU-induced apoptosis in vivo, we gave mice an i.p. injection of 5-FU. Apoptotic cell death peaked in thymocytes at 18 h after administration of 5-FU. Total organ weight and cell number in the thymus were reduced by approximately 40%. This cell loss was due to apoptosis, as measured in cell suspensions by measuring hypodiploid DNA content and by terminal deoxynucleotidyl transferase-mediated nick end labeling staining of tissue sections. The number of apoptotic cells correlated with the extent of weight loss and cell attrition of the organs. Furthermore, in the thymi of 5-FU-treated animals, CD95L was strongly up-regulated. Apoptosis of thymocytes was blocked in vivo with neutralizing anti-CD95L antibodies. In addition, cell loss in the thymus was negligible in lpr mice in comparison with wild-type mice. Thus, a significant portion of apoptosis of thymocytes in vivo on treatment with 5-FU is mediated via the CD95/CD95L pathway. Our findings therefore contribute to the understanding how chemotherapeutic drugs exert their effects in vivo.